Defective autophagy through epg5 mutation results in failure to reduce germ plasm and mitochondria. Issue 10 (16th July 2015) - Herpin, Amaury; Englberger, Eva; Zehner, Mario; Wacker, Robin; Gessler, Manfred; Schard, Manfred
ABSTRACT: Autophagy is an evolutionarily conserved catabolic process that transports cytoplasmic components to lysosomes for degradation. In addition to the canonical view of strict stress‐response‐induced autophagy, selectively programmed autophagy was recently reported in the context of gonad development of flies and worms, where autophagy seems to be necessary for clearance of germ plasm components. Similar functions have not been described in vertebrates. We used the medaka fish to study the role of autophagy in gonad formation and game to∗∗ genesis for the first time in a vertebrate organism for which the germ line is specified by germ plasm. Using a transgenic line deficient in the Ol‐epg5 gene—a new critical component of the autophagy pathway—we show that such deficiency leads to an impaired autophagic flux, possibly attributed to compromised maturation or processing of the autophagosomes. Ol‐epg5 deficiency correlates with selectively impaired spermatogenesis and low allele transmission rates of the mutant allele caused by failure of germ plasm and mitochondria clearance during the process of germ cell specification and in the adult gonads. The mouse epg‐5 homolog is similarly expressed in the maturating and adult testes, suggesting an at least partially conserved function of this process during spermatogenesis in vertebrates.—Herpin, A., Englberger, E., Zehner, M., Wacker, R., Gessler, M., Schartl, M. Defective autophagy through epg5 mutation results in failure to reduce germ plasm and mitochondria. FASEB J. 29, 4145‐4161 (2015). www.fasebj.org